Implementasi Tes Essay Dalam Evaluasi Pembelajaran Pendidikan Agama Islam - Nurul Latifatul Inayati; Anisha Nurul Fatimah; Salma Emilia Azzahra; Imaniar Risty Alamsyah (Pusat Riset dan Inovasi Nasional, 2024)
The challenges and development of education in Indonesia are getting bigger considering the rapid changes in the times. Evaluation is one of the competencies and a series of learning steps that a teacher must master and also aims to understand the basic concept of evaluation and its implications in evaluating Islamic Religious Education learning. Assessing learning through essay tests allows for a more in-depth assessment of students' understanding and skills. Essay tests give students the opportunity to present their thoughts and arguments in detail, allowing teachers to assess understanding of concepts more holistically. This article uses qualitative methods and approaches the study of book literature and previous research journals. The results of this research are that there are efforts to support the quality of education by holding good and correct evaluations and various choices to suit the type of learning. In this case, the essay test evaluation is a critical and more descriptive evaluation instrument.